2016
DOI: 10.1016/j.ajpath.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Neural Crest–Derived Progenitor Cells in Normal and Fuchs Endothelial Dystrophy Corneal Endothelium

Abstract: Human corneal endothelial cells are derived from neural crest and because of postmitotic arrest lack competence to repair cell loss from trauma, aging, and degenerative disorders such as Fuchs endothelial corneal dystrophy (FECD). Herein, we identified a rapidly proliferating subpopulation of cells from the corneal endothelium of adult normal and FECD donors that exhibited features of neural crestederived progenitor (NCDP) cells by showing absence of senescence with passaging, propensity to form spheres, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Most interestingly, these characteristics were determined not only on human corneal endothelial cells in an early and late passage but also on cells derived from FECD patients. 60 These results are suggestive, but although it is tempting to think that there may be an endothelial stem cell population, without human studies using cellular labeling in vivo, it is difficult to conclude with certainty if the corneal endothelial cells are proliferating or just enlarging and migrating.…”
Section: Is It Just Migration or True Proliferation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Most interestingly, these characteristics were determined not only on human corneal endothelial cells in an early and late passage but also on cells derived from FECD patients. 60 These results are suggestive, but although it is tempting to think that there may be an endothelial stem cell population, without human studies using cellular labeling in vivo, it is difficult to conclude with certainty if the corneal endothelial cells are proliferating or just enlarging and migrating.…”
Section: Is It Just Migration or True Proliferation?mentioning
confidence: 99%
“…82 Although neural crestederived progenitor cells also can be isolated from FECD eyes, the question remains whether the migrated and/or proliferated cells can function and, if so, for how long? 60 Currently, endothelial cell loss 1 year after conventional EK ranges between 30% and 50%, largely as a result of graft preparation and surgical manipulation. 6,12,66,70,94,117 A 5-year follow-up study revealed a mean loss of 53% of endothelial cells after EK, considerably lower than the 70% seen with PK, while graft survival was similar.…”
Section: The Need For Prospective Randomized Control Trialsmentioning
confidence: 99%
“…An enrichment of p75NTR (neurotrophin receptor) positive cells at the corneal endothelial side of the transition region between the corneal endothelium and the trabecular meshwork has been shown; however, no statistically significant difference was found in colony forming efficiency or number of p75NTR positive cells (Hara et al 2014). The presence of less differentiated cells and expression of stem cell markers in the extreme corneal endothelial periphery also has been described (He et al 2012; Katikireddy et al 2016). Our laboratory reported the presence of slow cycling cells in the murine endothelial extreme periphery (Espana et al 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, this remains a great challenge as CEC have a restricted proliferative ability in humans, limiting its feasibility [4]. Furthermore, donor corneas are generally from older patients and these cells present even lower proliferation rates, being more prone to senescence than younger corneas [5][6][7][8]. In order to overcome the senescence state of cells, a recent study cultured CEC from a young donor and injected them with ROCK inhibitor, which has been described to reduce intraocular pressure, to increase CEC cell density and to promote the typical polygonal monolayer phenotype [9,10].…”
Section: Introductionmentioning
confidence: 99%